Inter relationship between emotional intelligence and personality trait of educator leaders - Md Nawi, Nurul Hudani; Redzuan, Ma’rof; Hamsan, Hanina Halimatusaadiah (Human Resource Management Academic Research Society, 2012)
The main objective of this cross-sectional study is to determine inter relationship of emotional intelligence and personality trait (Conscientiousness, Openness to experiences, Extraversion, Agreeableness) among school educator leaders in High Performance Schools (SBT). Two sets of questionnaire to measure emotional intelligence and personality trait were administered to 306 (89%) subjects who were selected by stratified random sampling in 15 SBT schools in Malaysia. Data were analyzed through inferential statistics such as correlation. The finding by the bivariate analysis using the Pearson correlation method indicates that the personality trait such as Conscientiousness (r=.552, p<.05), Openness to experiences (r=.362, p<.05), Extraversion (r=.505, p<.05), Agreeableness (r=.193, p<.05) are positively and significant correlated with overall emotional intelligence among the schools educator leaders. The correlation values of the personality Conscientiousness trait (r=.552, p<.05) are higher than the correlation values of the rest of others personality traits and emotional intelligence. This finding suggests that personality Conscientiousness trait have stronger relationship with emotional intelligence compare to the others traits. On a practical note, the assessment of psychological construct in schools setting such as emotional intelligence and personality could possibly assist in enhancing the work performances in delivering huge benefits to the society especially in the educational contexts.